휘트니스센터 고객의 자기결정성과 관계몰입, 고객지향성, 서비스품질 및 관계지속의도와의 관계 - 김범; Buom Kim; 정정희; Jung-hee Jung (Ch'eyuk kwahak yŏn'gu, 2018)
[목적] 이 연구의 목적은 휘트니스센터 고객의 자기결정성 요인과 관계몰입, 고객지향성, 서비스품질 및 관계지속의도와의 관계를 구조방정식모형을 통해 실증적으로 분석하는 것이다. [방법] 서울지역에 소재한 5개소의 휘트니스센터 회원 242명을 대상으로 하였다. 표본추출은 편의표본추출법과 설문지작성은 자기기입식으로 하였다. 제안한 구조모형을 검증하기 위해 IBM SPSSWIN Ver. 21.0과 AMOS 18.0을 사용하였다. [결과] 첫째, 자율성은 관계몰입에 긍정적인 영향을 미쳤다. 둘째, 유능성은 관계몰입에 긍정적인 영향을 미치지 않았다. 셋째, 관계성은 관계몰입에 긍정적인 영향을 미쳤다. 넷째, 관계몰입은 고객지향성에 긍정적인 영향을 미쳤다. 다섯째, 관계몰입은 서비스품질에 긍정적인 영향을 미쳤다. 여섯째, 고객지향성은 관계지속의도에 긍정적인 영향을 미쳤다. 일곱째, 서비스품질은 관계지속의도에 긍정적인 영향을 미쳤다. [Purpose] The purpose of this research is to empirically analyze the relationship between self-determination and relationship commitment, customer orientation, service quality, and relation continuity intention of fitness center customers through structural equation model analysis. [Methods] For this purpose, this study set 242 members at the five fitness centers located in Seoul as the research subjects. In an effort to verify the proposed structural model, this study used IBM SPSSWIN Ver. 21.0 and AMOS 18.0. [Results] As a result, first, autonomy had a positive effect on relationship commitment. Second, competence didn’t had a positive effect on relationship commitment. Third, relatedness had a positive effect on relationship commitment. Fourth, relationship commitment had a positive effect on customer orientation. Fifth, relationship commitment had a positive effect on service quality. Sixth, customer orientation had a positive effect on relation continuity intention. Seventh, service quality had a positive effect on relation continuity intention.